Characterization of the aetiological agent of cow-pox with special reference to its biological properties - JANA, D; MEHROTRA, M L (The Indian Journal of Animal Sciences, 2013)
The cow-pox virus isolated from anatural outbreak of cow-pox was found pathogenic to a wide species of laboratory and domestic animals. The virus was easily adapted to in vitro systems, viz. chick embryo fibroblast, vero cell-lines and in vilro system, i.e. chorio-allantoic membranes of chicken embryo. There was steady increase In titres of Virus with adaptation. The presence of CPV in these systems was confirmed by its cytopathic effects, Indireci FAT and dot-enzyme-linked immunosorbent assays. Histopathology of the infected issues and the acidophilic intractoplasmic indusions found in the stained coverslip preparation. were characteristic of orthopox viruses. The virus agglutinated erythrocytes of poultry and turkey. but not of guineapig.